The Newest Three-Letter Fad in Health : Can HTA Escape the Fate of NHA, CEA, GBD? - Yazbeck, Abdo S. (Taylor and Francis, 2016)
The January 2016 issue of Health Systems and Reform, “Special Issue: Prince Mahidol Award Conference 2016: Priority Setting for Universal Health Coverage, offers some hope for prioritization in health. The issue included several commentaries and articles that urge a balanced approach to prioritization, while others explore the limitations of empirical tools like cost effectiveness and HTA. The main question for me is the following: Will the zeal for a technical answer win over the more pragmatic commentary presented in these articles of HS&R?